The local-orbifold correspondence for simple normal crossings pairs - Battistella, Luca; Nabijou, Navid; Tseng, Hsian-Hua; You, Fenglong (Arxiv, 2021)
For X a smooth projective variety and D=D1+…+Dn a simple normal crossings divisor, we establish a precise cycle-level correspondence between the genus zero local Gromov-Witten theory of the bundle ⊕ni=1OX(−Di) and the maximal contact Gromov-Witten theory of the multi-root stack XD,r⃗ . The proof is an implementation of the rank reduction strategy. We use this point of view to clarify the relationship between logarithmic and orbifold invariants.